Language-Paradox-Poetics : A Chinese Perspective - Liu, James J. Y. (Book collections on Project MUSE., 2014)
In attempting to define a ""poetics of paradox"" from a traditional Chinese standpoint, James Liu explores through a comparative approach linguistic, textual, and interpretive problems of relevance to Western literary criticism. Liu's study evolves from a paradoxical view--originating from early Confucian and Daoist philosophical texts--that the less is ""said"" in poetry, the more is ""meant."" Such a view implied the existence of paradox in the very use of language and led traditional Chinese hermeneutics to a study of ""metaparadox""--The use of language to explicate texts the meaning of